THE NEGATIVE EFFECTS OF TWO-STATE CONFLICTS ON THE GLOBAL ECONOMY - Akramov, Izzatillo Murodjon o‘g‘li (Educational Research in Universal Sciences, 2023)
This article talks about the factors affecting the world economy behind the current problems between the two countries. Opinions were also given on the extent to which this conflict is rapidly escalating and on the important areas that will not have negative effects in the future.